Studies on Microbial Quality, Protein Yield, and Antioxidant Properties of Some Frozen Edible Insects - Peter Kurdi; Patspon Chaowiwat; Jirathit Weston; Chanida Hansawasdi (International Journal of Food Science)
This research investigated the microbial quality and the protein contents of Thai commercial frozen products of silkworm (Bombyx mori), bamboo caterpillar (Omphisa fuscidentalis), and field cricket (Gryllus bimaculatus). Total mesophilic aerobic counts were about 8-8.4 log cfu/g, while lactic acid bacteria numbers were up to 5.2 log cfu/g samples. Yeasts and mold as well as Enterobacteriaceae numbers were found to be no more than 6.3 and 6.6 log cfu/g, respectively, while Clostridium spp. enumeration detected 3.2-3.6 cfu per gram frozen insect samples. The protein content in cases of cricket and bamboo caterpillar after the Soxhlet defatting method and the Folch lipid extraction combined with isoelectric point precipitation were similar when compared at pH 3.5 or pH 4.5. In contrast, the protein yield from silkworm was higher at pH 3.5 in the Soxhlet defatted sample, as opposed to the Folch method treated sample where higher protein yield was obtained at pH 4.5. Furthermore, 2,2-diphenyl-1-picryl-hydrazyl (DPPH) radical scavenging activity and ferric reducing antioxidant power (FRAP) of field cricket subcritical water (121 or 135°C for 15 or 30 minutes) hydrolysates were also measured on a pilot basis. These tests revealed higher antioxidant activities in treated samples than in the untreated control. The highest DPPH radical scavenging activity and FRAP values were detected in samples treated at 135°C, while the protein content of these samples was lower than that of the untreated control. These results indicate that hydrolytic compounds of proteins and probably other types of cricket materials are possibly involved in the antioxidant activities of the treated defatted cricket samples.